THE INFLUENCE OF SOLAR COLLECTOR APPLICATIONS ON THE ECONOMICS OF DOMESTIC HOT WATER PRODUCTION - Gołębiowska, Justyna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
One of the principal actions arising from the need for rational energy management, is the increase of renewable energy sources use. Application of solar energy photothermal conversion for domestic hot water preparation is a solution that, by reducing demand for conventional energy, allows to minimize the cost of system operation effectively. In this paper, a performance of solar hot water installation working in a typical apartment building is analyzed. The building is located in Lublin, in the third climate zone. Energy demand for heating domestic water was monitored in 2010–2013. The operational effects of the system were compared in terms of energy and cost with the most commonly used systems for domestic hot water heating.